2020
DOI: 10.1002/anie.202000740
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Pronged Attack by Homologous Far‐red/NIR AIEgens to Achieve 1+1+1>3 Synergistic Enhanced Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) has long been shown to be a powerful therapeutic modality for cancer. However, PDT is undiversified and has become stereotyped in recent years. Exploration of distinctive PDT methods is thus highly in demand but remains a severe challenge. Herein, an unprecedented 1+1+1>3 synergistic strategy is proposed and validated for the first time. Three homologous luminogens with aggregation‐induced emission (AIE) characteristics were rationally designed based on a simple backbone. Through sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 164 publications
(112 citation statements)
references
References 33 publications
(13 reference statements)
2
109
0
Order By: Relevance
“…AIE refers to a unique phenomenon that some fluorophores are nonemissive or weakly emissive in the molecularly dissolved state but they emit intensively in aggregates due to the restriction of intramolecular motions (RIM). [ 29–33 ] Ascribe to their intrinsic advantages including bright emission in aggregates, high photobleaching threshold, and high signal‐to‐noise ratio, AIE luminogens (AIEgens) represent a class of extraordinary alternatives for constructing luminescent supramolecular materials. The utilization of AIEgens not only straightforwardly provides valuable insights in mechanistic understanding of supramolecular chemistry, but also powerfully functionalizes supramolecular materials with efficient fluorescence, making AIEgens‐based supramolecular materials highly useful in sensing, bioimaging, and optoelectronic devices.…”
Section: Figurementioning
confidence: 99%
“…AIE refers to a unique phenomenon that some fluorophores are nonemissive or weakly emissive in the molecularly dissolved state but they emit intensively in aggregates due to the restriction of intramolecular motions (RIM). [ 29–33 ] Ascribe to their intrinsic advantages including bright emission in aggregates, high photobleaching threshold, and high signal‐to‐noise ratio, AIE luminogens (AIEgens) represent a class of extraordinary alternatives for constructing luminescent supramolecular materials. The utilization of AIEgens not only straightforwardly provides valuable insights in mechanistic understanding of supramolecular chemistry, but also powerfully functionalizes supramolecular materials with efficient fluorescence, making AIEgens‐based supramolecular materials highly useful in sensing, bioimaging, and optoelectronic devices.…”
Section: Figurementioning
confidence: 99%
“…[ 58,59 ] For instance, lots of AIE PSs have been reported to exhibit much higher ROS generation efficiency than the renowned PS Rose Bengal (RB). [ 22,44,82 ] Additionally, as hydrophobic organic molecules naturally aggregate in aqueous medium and are usually utilized in theranostics in the form of NPs, AIEgens offer the unique opportunity to form nanoaggregates or NPs with high emission brightness and efficient ROS production. Most attractively, AIE NPs display almost linear loading‐dependent increase in both brightness and ROS generation efficiency, which is essentially distinct from ACQ PSs‐based NPs that exhibit compromised brightness and photosensitization at high loading density [60] .…”
Section: Aggregation‐induced Superiorities Of Aiegens In Theranosticsmentioning
confidence: 99%
“…[ 22–24 ] Additionally, it has been demonstrated that AIEgens can generally produce ROS efficiently in aggregates, enabling their application of high‐performance FLI‐guided PDT. [ 25–30 ] Although the emergence of AIE PSs has indeed triggered state‐of‐the‐art development of FLI‐guided PDT with initial success in the past few years, some major problems have yet to be solved. For instance, it is difficult to simultaneously achieve effective ROS generation and strong emission with long wavelength; [ 31,32 ] furthermore, combining well‐performed AIE PSs with functional nanomaterial to improve their versatility and to develop novel multifunctional theranostic nanoplatform for advanced anticancer therapeutics is urgently needed.…”
Section: Figurementioning
confidence: 99%